2018
DOI: 10.1021/acs.jpca.8b00261
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electron-Donating and Electron-Withdrawing Groups in Tuning the Optoelectronic Properties of Difluoroboron–Napthyridine Analogues

Abstract: Five napthyridine-based fluorine-boron (BF-napthyridine) conjugated compounds have been theoretically designed, and subsequently, their photophysical properties are investigated. The influence of electron-donating and electron-withdrawing groups attached with the NCO moiety of BF-napthyridine molecule has been interpreted. The optoelectronic properties, including absorption spectra and emission spectra of the BF-napthyridine derivatives are studied using density functional theory (DFT) and time-dependent densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…The increment of the electron affinity values with the increase of EWGs in the compounds indicates the enhancement electron transfer nature. 52 High EA (adiabatic) (>2.80 eV) and low LUMO energy level (<À4.00 eV) are the important parameters for ambient airstability and n-type behaviour of organic semiconductors. 53,54 In our study, it is found that purely alkyl substituted NDIs (1a, 1b, 1c, 1d) have EA value less than 2.8 eV and LUMO levels higher than À4.00 eV.…”
Section: Electron Affinity (Ea) and Ionization Potential (Ip)mentioning
confidence: 99%
“…The increment of the electron affinity values with the increase of EWGs in the compounds indicates the enhancement electron transfer nature. 52 High EA (adiabatic) (>2.80 eV) and low LUMO energy level (<À4.00 eV) are the important parameters for ambient airstability and n-type behaviour of organic semiconductors. 53,54 In our study, it is found that purely alkyl substituted NDIs (1a, 1b, 1c, 1d) have EA value less than 2.8 eV and LUMO levels higher than À4.00 eV.…”
Section: Electron Affinity (Ea) and Ionization Potential (Ip)mentioning
confidence: 99%
“…Using quinine sulfate as reference, the fluorescence quantum yields of MHHNA and PU-MHNNA were measured to be 0.71. Meanwhile, λ ex (421 nm) and λ em (522 nm) of PU-DHHNA were also the same as that of DHHNA, thus generating a larger Stokes shift (101 nm), because the diethylamino group possessed stronger electron donating ability than the methoxy group, causing a higher intramolecular charge transfer rate and a smaller energy gap between HOMO and LUMO [32,33]. Furthermore, it is worth noting that at the same fluorophore concentration (3 × 10 –2 mM), PU-DHHNA displayed enhanced fluorescence intensity in emission and excitation spectra, and its quantum yield (0.15) was considerably increased compared with DHHNA (0.08) (Figure 2C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the electrophilicity around the boron center is expected to result in enhanced nucleophilic binding to boron. [8,50,51] pK a determination studies of deprotected 3 f (5 a) showed two inflection points of 3.4 and 8.1 (Figure 3 a).…”
Section: Angewandte Chemiementioning
confidence: 97%